Smoking status moderates the association of the dopamine D4 receptor (DRD4) gene VNTR polymorphism with selective processing of smoking-related cues. - Munafò, MR; Johnstone, E (2008)
Recently, a variable number of tandem repeats (VNTR) polymorphism in the dopamine D4 receptor (DRD4) gene has been reported to be associated with greater craving and more attention to smoking cues, following a cue-elicited craving procedure. We investigated whether the DRD4 VNTR 7-repeat polymorphism is associated with selective processing of smoking-related stimuli, using a modified Stroop task, and whether smoking status moderates this association. Thirty-one current smokers and 17 ex-smokers attended a single testing session and completed the modified Stroop task. The experimental design included two between-subjects factors of smoking status (current smoker, ex-smoker) and DRD4 genotype (short, long). The DRD4 VNTR polymorphism was associated with selective processing of smoking-related stimuli in ex-smokers but not in current smokers. Our data, therefore, provide partial support for our primary hypothesis and extend on previous work which suggests a role for variation at the DRD4 locus in modulating reactivity to drug-related cues.